2009
DOI: 10.1002/pssc.200880839
|View full text |Cite
|
Sign up to set email alerts
|

Low resistance ohmic contacts annealed at 600 °C on a InAlN/GaN heterostructure with SiCl4‐reactive ion etching surface treatment

Abstract: In this paper, the effect of the surface treatments on the performance of Ti/Al/Ni/Au ohmic contacts to InAlN/GaN has been investigated by electrical characterization and by normalized Auger electron spectroscopy (AES). Contact resistance and specific contacts resistivity as low as 0.7 Ωmm and 1.1×10–7 Ωcm2, respectively, have been achieved by pre‐treatment using SiCl4 plasma followed by rapid thermal annealing at at 600 °C. This is compared with the case where no plasma pre‐treatment was performed. Contacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Nitride formation is mainly driven by the change in enthalpy. 21,22 However, these contacts necessitate premetal deposition surface treatment by plasma to render ohmic properties. [16][17][18][19][20] Furthermore, these transition metals (TMs) have more negative enthalpies for nitride formation than GaN (À26.3 kcal/mol), which means the transition metal nitride formation is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Nitride formation is mainly driven by the change in enthalpy. 21,22 However, these contacts necessitate premetal deposition surface treatment by plasma to render ohmic properties. [16][17][18][19][20] Furthermore, these transition metals (TMs) have more negative enthalpies for nitride formation than GaN (À26.3 kcal/mol), which means the transition metal nitride formation is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Next, photolithography of the ohmic contacts is used to create a resist pattern for both of recessing and deposition of the ohmic contact metallization. It has been suggested earlier to use SiCl 4 -based reactive ion etching (in-situ) before forming ohmic contacts on InAlN to reduce the temperature of annealing [7]. Our recessing was doing using the argon sputtering (ex-situ).…”
Section: Contributed Articlementioning
confidence: 99%
“…The contact resistance was about 0.358 Ω•mm with a low annealing temperature of 500 • C. They found that thinner Ti layer can lead to a lower annealing temperature, because Al needs to diffuse through the Ti layer in order to make Ohmic contact with AlGaN. Pozzovivo et al [84] studied the effects of a special SiCl 4 plasma treatment prior to the Ohmic metallization. They achieved a sufficiently low contact resistance of 0.7 Ω•mm at a reduced anneal temperature of 600 • C. The contact surfaces of AlGaN were directly treated by the SiCl 4 plasma for 15 s in RIE with self-induced bias of about 300 V. They suggested that the SiCl 4 plasma treatment of AlGaN surface would help to enhance the generation of N vacancies, which may be responsible for the high carrier concentration at the AlGaN surface to form a low contact resistance.…”
Section: Ohmic Contacts For Source and Drainmentioning
confidence: 99%